Reporting Intellectual Capital In Annual Reports From Australian S/W & I/T Companies - Joshi, Mahesh; Singh Ubha, Dharminder; Sidhu, Jasvinder (Journal of Knowledge Management Practice, 2010)
This study examines the annual reports of the top 20 software and information technology companies listed on the Australian Stock Exchange, using the content analysis method. The findings of this study indicate that the levels of Intellectual capital disclosures are found to be low and are reported in qualitative form rather than quantitative form. The results of the study highlight that software and information technology companies in Australia do not attach importance to disclosing voluntary intellectual capital information. This study emphasises the need for an established and generally accepted framework for the reporting of intellectual capital to enable measurability and presentation of intellectual capital information in the annual reports.